A vertigo network derived from human brain lesions and brain stimulation. Issue 2 (17th March 2023) - Li, Yanran; Qi, Lei; Schaper, Frédéric L W V J; Wu, Di; Friedrich, Maximilian; Du, Jialin; Yu, Tao; Wang, Qiao; Wang, Xiaopeng; Wang, Di; Jin, Guangyuan; Liu, Aihua; et al.
Abstract: Vertigo is a common neurological complaint, which can result in significant morbidity and decreased quality of life. While pathology to peripheral and subtentorial brain structures is a well-established cause of vertigo, cortical lesions have also been linked to vertigo and may lend insight into relevant neuroanatomy. Here, we investigate the supratentorial lesion locations associated with vertigo and test whether they map to a common brain network. We performed a systematic literature search and identified 23 cases of supratentorial brain lesions associated with vertigo. We mapped the lesion locations to a standard brain template and computed the network of brain regions functionally connected to each lesion location, using a 'wiring diagram' of the human brain termed the human connectome ( n = 1000). Sensitivity was assessed by identifying the most common connection to lesion locations associated with vertigo, and specificity was assessed through comparison with control lesions associated with symptoms other than vertigo ( n = 68). We found that functional connectivity between lesion locations and the bilateral ventral posterior insula was both sensitive (22/23 lesions) and specific (voxel-wise family-wise error-corrected P < 0.05) for lesion-induced vertigo. We computed connectivity with this hub region to define a lesion-based vertigo network, which included regions in the bilateral insula, somatosensory cortex, higher-level visual areas, cingulate sulcus, thalamus and multiple cerebellar regions in the territory of the posterior inferior cerebellar artery. Next, we used stereo-electroencephalography (80 stimulation sites across 17 patients) to test whether stimulation sites associated with vertigo mapped to this same network. We found that 36/42 (86%) of stimulation sites eliciting vertigo fell within the lesion-based vertigo network in contrast to 16/39 (41%) of stimulation sites that did not elicit vertigo. Connectivity between stimulation sites and our lesion-based hub in the ventral posterior insula was also significantly associated with vertigo ( P < 0.0001). We conclude that cortical lesions and direct electrical stimulation sites associated with vertigo map to a common brain network, offering insights into the causal neuroanatomical substrate of vertigo. Abstract : Vertigo is a common neurological complaint, affecting almost all people at some point during their life span. Li et al . showed a cortical vertigo network derived from brain lesions and the intracranial direct electrical stimulation sites, which offers new insights into the neuroanatomical substrate of vertigo. Graphical Abstract: Graphical Abstract Video Abstract: